C-reactive protein and statins in heart failure with reduced and preserved ejection fraction - Park, Jin Joo; Yoon, Minjae; Cho, Hyoung-Won; Cho, Hyun-Jai; Kim, Kye Hun; Yang, Dong Heon; Yoo, Byung-Su; Kang, Seok-Min; Baek, Sang Hong; Jeon, Eun-Seok; Kim, Jae-Joong; Cho, Myeong-Chan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background High C-reactive protein (CRP) levels are associated with poor outcomes of heart failure (HF), and statins are known to reduce CRP levels. We investigated the prognostic value of CRP and statin in patients with HF with reduced and preserved ejection fraction (EF). Methods Altogether, 3,831 patients from the Korean Acute Heart Failure registry were included and stratified according to the tertiles of CRP levels (T1: CRP < 0.30 mg/dL, T2: 0.30–1.14 mg/dL, and T3: CRP > 1.14 mg/dL). HF with reduced EF (HFrEF), HF with mildly reduced EF (HFmrEF), and HF with preserved EF (HFpEF) were defined as left ventricular ejection fraction (LVEF) ≤ 40%, 41–49%, ≥50%, respectively. The primary endpoints were all-cause, in-hospital, and post-discharge mortality. Results No significant correlation was observed between CRP levels and LVEF (r = 0.02, P = 0.131). The prevalence of risk factors increased gradually from T1 to T3 in both the types of HF. Overall, 139 (3.6%) and 1,269 (34.4%) patients died during the index admission and follow-up (median: 995 days), respectively. After adjustment, each increase in the CRP tertiles was independently associated with in-hospital mortality (HFrEF: OR 1.58 and 95% CI 1.09–2.30, HFmrEF: OR 1.51 and 95% CI 0.72–3.52, and HFpEF: OR 2.98, 95% CI 1.46–6.73) and post-discharge mortality (HFrEF: HR 1.20, 95% CI 1.08–1.33, HFmrEF: HR 1.38 and 95% CI 1.12–1.70, and HFpEF: HR 1.37, 95% CI 1.02–1.85). In only patients with LVEF > 40% with highest CRP tertile, statin-users showed better survival trend than those without statins. Conclusion CRP is an excellent prognostic marker for HFrEF, HFmrEF, and HFpEF, implying that the neurohumoral and inflammatory pathways might be independent pathways. Statins may be beneficial in HF patients with increased CRP levels. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT013 89843].